2011
DOI: 10.1128/cvi.00358-10
|View full text |Cite
|
Sign up to set email alerts
|

Successful Memory Response following a Booster Dose with a Virosome-Formulated Hepatitis A Vaccine Delayed Up to 11 Years

Abstract: Boosting adult travelers with the virosome-formulated, aluminum-free hepatitis A vaccine Epaxal up to 128 months after a single primary dose confers full protection against hepatitis A, even in travelers aged 50 years and above. Delaying the booster dose did not influence the immune memory response to Epaxal.Adults traveling from regions where the prevalence of hepatitis A is low to regions where it is high are at risk of acquiring symptomatic hepatitis A virus (HAV) infection (1). Long-lasting protection agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 11 publications
2
28
0
Order By: Relevance
“…Information on long-term persistence after administration of a single dose of vaccine in children is limited, but has been documented in adults 76-78 . This information would suggest that protective anti-HAV antibody levels after a single dose of inactivated hepatitis A vaccine can persist for up to 11 y.…”
Section: Discussionmentioning
confidence: 99%
“…Information on long-term persistence after administration of a single dose of vaccine in children is limited, but has been documented in adults 76-78 . This information would suggest that protective anti-HAV antibody levels after a single dose of inactivated hepatitis A vaccine can persist for up to 11 y.…”
Section: Discussionmentioning
confidence: 99%
“…A single dose schedule would remove barriers to the use of these vaccines for public health purposes by reducing the cost associated with immunization. The efficacy and safety of both one-and two-dose inactivated HAV vaccines have already been established [11][12][13][14][15]. At present, two Latin American countries have adopted single dose hepatitis A childhood immunization programs.…”
Section: Introductionmentioning
confidence: 99%
“…Two of the longest follow-up studies in adults reported the persistence of anti-HAV antibodies up to at least 17 years after receiving a monovalent inactivated HAV vaccine (Havrix TM , GlaxoSmithKline Vaccines, Belgium) according to a two-dose schedule. Hens and colleagues [44] projected duration of protection of at least 25 years in ≥95% of the vaccines [10,14,15]. However, only humoral responses have been considered when verifying protection; cellular responses have not been assessed.…”
Section: Introductionmentioning
confidence: 99%
“…16 One study showed a memory response up to 11 y with a booster dose of virosome-formulated inactivated hepatitis A vaccine. 17 A memory response was also seen in children who had waning immunity following H 2 vaccination and had become seronegative. These children showed a robust antibody response when vaccinated 6 y following their initial H 2 vaccine immunization.…”
Section: Discussionmentioning
confidence: 91%